MR of brain radiation injury: experimental studies in cats. - Hecht-Leavitt, C; Grossman, R I; Curran, W J; McGrath, J T; Biery, D N; Joseph, P M; Nelson, D F (American Journal of Neuroradiology, 1987)
Two of six cats receiving small-field, single-dose, brain irradiation of 35 Gy with 6 MeV photons developed brain abnormalities in the irradiated area on MR images at 6 and 8 months, respectively, after treatment. The lesions were of high intensity on T2-weighted images and did not enhance after IV administration of gadolinium-DTPA. An additional lesion in one of these cats displayed high signal on T2-weighted images and enhanced on T1-weighted images after IV gadolinium-DTPA. Pathologic correlation revealed that the nonenhancing T2-weighted lesions consisted of edema or demyelinated regions without inflammation while the gadolinium-enhanced lesion demonstrated necrosis with inflammatory infiltrate. Focal brain irradiation may produce noninflammatory demyelination and necrosis. These histologic entities may be potentially distinguished on MR with IV gadolinium-DTPA.